Language Endangerment In Southwestern Burkina: A Tale Of Two Tiefos - Hantgan-Sonko, Abbie (My University, 2018)
Most of the thirty or so small-population languages of southwestern Burkina Faso are still reasonably viable in spite of the spread of Jula as the dominant regional vernacular. An unusual case is Tiefo, which is really two distinct but closely related and geographically contiguous Gur languages. One, here dubbed Tiefo-N, was spoken in the villages of Noumoudara and Gnanfongo (Nyafogo). The other, Tiefo-D, was spoken in the nearby village cluster of Dramandougou. Several other ethnically Tiefo villages in the zone had already been completely Jula-ised by the mid-20th Century. Tiefo-N is moribund (a handful of ageing semi-speakers in Gnanfogo, none in Noumoudara), the villagers having gone over to Jula. By contrast, Tiefo-D is in a relatively comfortable bilingual relationship to Jula and is still spoken to some extent even by children, though everyone also speaks Jula. This paper clarifies the relationship between Tiefo-N and Tiefo-D and addresses the question why the two languages have had such different fates
Keywords: Language endangerment; Southwestern Burkina; Tiefo